Apport de diverses sources de données à la réalisation d’une intervention ergonomique - Marie St-Vincent; Denys Denis; Daniel Imbeau; François Ouellet (Perspectives Interdisciplinaires sur le Travail et la Santé)
The study presented is a methodological reflection on the ergonomic intervention process. The study’s objectives were to specify the contribution of nine sources of data to an ergonomic intervention. A posteriori follow-up was done on an intervention field study aiming to reduce MSDs in a warehouse superstore in the retail sales sector. Nine sources of data classically used in ergonomics were analyzed: questionnaires, interview data, observation data. Interview data were found to provide more information and cover more topics than observation data. However, the latter are more precise. Individual interview data and autoconfrontations are more meaningful because they provide more links between the different topics covered. Interview data contribute to the social construction of the intervention and to the evolution of the participants’ representations. Observation data, because they are quantified, have the power to convince the employer of the severity of the different problems. The majority of the information collected by the different sources was found to be new information (54.7%), while less was clarifications (34.6%), and only 11% was confirmations. As a result, learning continues throughout the analysis of the various sources of data. The ergonomic diagnosis must therefore be considered as progressively becoming more precise through the different data sources by a gradual construction of the information throughout the intervention. The conclusion assesses the study’s contribution. The authors believe that the study initiates profound reflection, used as a basis in specifying the main characteristics, advantages and limitations of the different sources of data in the context studied. From this perspective, ergonomists, practitioners and researchers can benefit greatly from this study.